Genetic screening for pheochromocytoma: should SDHC gene analysis be included?. Issue 9 (8th June 2007) - Mannelli, M; Ercolino, T; Giachè, V; Simi, L; Cirami, C; Parenti, G
Abstract : PGL3 syndrome is caused by mutations in the SDHC gene. At present, only a few families affected by SDHC mutations have been reported in the literature and in each of them the clinical presentation was characterised by paragangliomas located only in the head and neck regions. No evidence of thoracic or abdominal catecholamine-secreting chromaffin tumours has been reported to date. We report the case of a 15-year-old girl with hypertension and a norepinephrine-secreting abdominal paraganglioma who was found to harbour a novel nonsense SDHC mutation, demonstrating that the clinical presentation of PGL3 syndrome can be more diverse than expected.